Identifikasi Pelaksanaan Pembelajaran Matematika pada Era New Normal dengan Aplikasi Google Classroom - Arosi, Jaesi Aulia; Wijayanti, Dyana; Ubaidah, Nila; Lutfi, Ahmad (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to determine how the use of features in the Google Classroom application in online mathematics learning during the Covid-19 pandemic in one of the public secondary schools in Demak Regency in the 2021/2022 academic year. The instruments used were questionnaires and interview guidelines. The questionnaire contains statements about 21 features presented in the form of feature names and images of features. The questionnaire used in this study uses a Likert scale with choices consisting of always, often, sometimes, never, and never. Interviews were conducted to find out the teachers' reasons for not maximising the use of some Google Classrooom features as online learning media. The research method used was descriptive-quantitative. Data analysis used descriptive statistics, namely the average, then classified by category. The results of this study show that there are several features that have been optimised for use and there are also features that have not been optimally used. Features that have a high percentage of use are, share assignments, share materials, share notes with a percentage of 100% each. Meanwhile, features that have a low percentage of use are 4 features, namely the discussion feature, poll feature, feedback feature, and learning video sharing feature with a percentage of 32%, 40%, 48%, 36% respectively. Overall, the utilisation of Google Classroom features in online mathematics learning is 66% which is included in the medium category.